Epithelioid sarcoma of femoral nerve – A case report - Ivanov, Dejan; Živojinov, Mirjana; Ranisavljević, Milan (Vojnosanitetski pregled, 2020)
Introduction. Epithelioid sarcoma is a slow-growing malignant soft tissue tumor and occurs approximately in 1% of all soft tissue malignant tumors. This case report describes epithelioid sarcoma in femoral nerve and as we know it is the first described case of epithelioid sarcoma at this anatomical localisation. Case report. A 44-years-old female patient presented with strong pain in her left leg. On magnetic resonance imaging (MRI), tumor was presented as a node 8 cm in the diameter at left femoral nerve between ileopsoas and iliacus muscle, without infiltration of muscle fascia and tendons. Four enlarged lymph nodes described in left iliac fosa, were suspected on secondary tumor deposits. We preformed radical surgical excision of the tumor and femoral nerve transection with local lymp hnode disection. Histopathological analysis revealed epithelioid sarcoma, and tumor stained highly positive for anti-pan cytokeratin antibody (AE1/AE3), vimentin, cancer antigen 125 (CA125), anti-cytokeratin antibody (MNF116), hematopoietic progenitor cell antigen (CD34) and epithelial membrane antigen (EMA) markers. After the operation patient recived radiotherapy without chemotherapy. Six months postoperatively, there was no evidence of local relapses or distant metastases. Conclusion. Initial wide surgical resection and adjuvant radiotherapy is beneficial in treatment of epitheloid sarcoma.